Anachronism of the True: Reading "Reading Capital" - Romé, Natalia (2017)
This essay explores the vitality of an Althusserian reading of "Capital" by means of a reconsideration of the so-called “theoreticism”. In this sense, I propose to approach the Althusserian intervention in the terms of a proper materialist query about practices. Following the idea posed by Etienne Balibar about the philosophical worth of Marxist theory in XXI century, I develop the thesis that in the light of Marxist “philosophy”, the misunderstood relation still existing between theoretical and political practices are nevertheless thinkable. Finally, I propose that in as much as it might be considered that in this relation lies the kernel of Marx’s discovery, it also could be a basis for rereading "Capital" under present challenges.